Challenges encountered among community-delivered malaria volunteers in Greater Mekong Sub-region for malaria elimination: a systematic review - Shwe, Nanda L.; Hlaing, Thein; Tun, Kyaw M. (International Journal Of Community Medicine And Public Health, 2022)
In the Greater Mekong Sub-region (GMS) countries, community-delivered malaria volunteers (CDMVs) have been serving a vital role in providing primary preventive and curative services of malaria in the uncovered areas, but they have encountered different challenges. The main purpose of this systematic review was to determine the CDMVs’ challenges in malaria elimination settings of the GMS. A review team applied MEDLINE and PubMed, Google Scholar, and Myanmar Health Sciences Research Journal as major databases and Boolean operators as the focus search for selecting a final set of 46 English studies designed with qualitative and quantitative, and published in 2010 and after. The service qualities of CDMVs were affected by different challenges: motivational challenges (lack of incentive pay, supervision, shortage of malaria supply and inadequate training), community acceptance challenges (negative comments and less preference of community, unawareness of the CDMVs' roles, and inappropriate care of traditional healers), technical challenges (unsatisfactory knowledge and practices, complexities of reporting formats and applications), communication and transportation challenges (lack of electricity and Internet, inapplicability of transportation aids and poor road infrastructure), safety challenges (testing blood with unsafe technique), financial and logistic supply challenges (lack of supply for additional costs, and interruption of malaria ‘supply’) challenges in malaria management (difficulties in managing the patients with mixed malaria, invalid RDT results and severe patients). This review recommends that more research on the community malaria services should be invited and the malaria programmers from each GMS country should establish more perfect volunteer policies for eliminating the CDMVs’ challenges.